A Companion to Medieval Toledo - Yasmine Beale-Rivaya; Jason Busic (Volume Editors)
1 online resource.
Keywords: A Companion to Medieval Toledo. Reconsidering the Canons explores the limits of “Convivencia” through new and problematized readings of material familiar to specialists and offers a thoughtful initiation for the non-specialist into the historical, cultural, and religious complexity of the iconic city of Toledo. The volume seeks to understand the history and cultural heritage of the city as a result of fluctuating coexistence. Divided into three themed sections,- the essays consider additional material, new transcriptions, and perspectives that contribute to more nuanced understandings of traditional texts or events. The volume places this cultural history and these new readings into current scholarly debates and invites its readers to do the same.